Comparison of safety of clindamycin (1%) - benzoyl peroxide (5%) combination gel with adapalene (0.1%) - benzoyl peroxide (2.5%) combination gel in treatment of mild to moderate facial acne vulgaris: A randomized prospective study (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Pathogenesis of acne vulgaris is complex and and multifactorial. Topical combination therapy can target multiple pathogenic mechanisms and therefore is currently recommended as the standard treatment of mild-to-moderate acne vulgaris. Various clinical studies have assessed the efficacy and safety of combination therapy for acne & demonstrated significantly greater and faster results with the combination therapy.Objective: The aim of this study was to compare the safety of clindamycin (1%) - benzoyl peroxide (5%) combination gel with adapalene (0.1%) - benzoyl peroxide (2.5%) combination gel in treatment of mild to moderate facial acne vulgaris.Methods: A prospective, randomized and comparative study was conducted on diagnosed cases of facial acne vulgaris attending outpatient department of Dermatology & Venereology, Dhaka National Medical College & Hospital, Dhaka. A total of 60 patients of acme were selected as per inclusion & exclusion criteria and randomly divided into two groups, 30 patients in group A and 30 patients in group B. Clindamycin (1%)-benzoyl peroxide (5%) combination gel was given for 12 weeks in the group A, while adapalene (0.1%) -benzoyl peroxide (2.5%) combination gel was given to the group B patients for same duration. All the drugs were provided in the gel form. The safety of the drugs were evaluated at week 2, 4, 8 and 12 weeks follow up. Safety and tolerability were assessed through evaluations of facial tolerability and adverse events. At each visit, any adverse effects like dryness, desquamation, erythema, burning sensation and irritation noted. All parameters were compared between two groups. Quantitative data was expressed as mean±SD. Values of the different parameters was compared to see the difference between two groups by using Chi-square test (x2). p0.05 was taken as non significant. 95% confidence limit was taken as the level of significance.Results: In the present study, side effects were observed in 40% of study subjects in C/BPO group & 66.66% in A/BPO group. Side effects observed in C/BPO group were dry skin 10%, desquamation 6.7%, burning sensation 3.3%, erythema 0% & irritation 3.3%. In A/BPO group, side effects were dry skin 13.3%, desquamation 13.3%, burning sensation 10%, erythema 3.3% & irritation 3.3%. There was no statistically significant mean difference was found between two groups (p>0.05), indicating adverse events & cutaneous toleribility of C/BPO were similar to A/BPO combination gel.Conclusion: Adapalene (0.1%) - Benzoyl peroxide (2.5%) combination gel & Clindamycin (1%) - Benzoyl peroxide (5%) combination gel both are well tolerated & having similar safety profile for the treatment of mild to moderate facial acne vulgaris.J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 35-39